(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
The Acephate is an organophosphorous insecticide of broad spectrum used in field crops. The easy availability of Acephate is generally encountered in forensic cases. The aim of present paper is to describe symptoms, postmortem changes occur in a reported case of Acephate insecticide and detection and identification of insecticide in visceral material by T.L.C.